Iatrogenic sciatic nerve injury: a case report - Devaraj, Navin Kumar; Abdul Rashid, Aneesa; Ali, Hanifatiyah (University of Malta, 2020)
Sciatic nerve injury is an uncommon presentation seen in primary care. Detailed history and careful physical examination may sometimes be able to elicit this diagnosis and possible cause. Sometimes additional imaging modality such as ultrasound or magnetic resonance imaging may be needed to confirm the diagnosis. This case report will look at a case of 60 years old woman who presented with severe pain and limping over her right lower limb which eventually linked to intramuscular injection given two days earlier for severe knee pain.